Legal Protection and Law Enforcement: The Unfinished Works - Arifin, Ridwan (Universitas Negeri Semarang, 2020)
Indonesia's legal system continues to grapple with challenges in ensuring effective legal protection and law enforcement. Despite significant reforms, inconsistencies in legal interpretation, weak institutional frameworks, and issues of corruption persist. This paper examines the ongoing gaps in legal protection, focusing on access to justice, human rights enforcement, and the effectiveness of law enforcement agencies. It highlights the role of legal institutions, including the judiciary, law enforcement bodies, and regulatory agencies, in upholding the rule of law. The study also explores key legal reforms undertaken to enhance legal certainty and the challenges faced in their implementation. Furthermore, the paper critically assesses the impact of international legal standards on Indonesia’s domestic legal framework, particularly in addressing transnational crimes, corporate accountability, and public governance. Drawing on case studies and recent legal developments, this research argues that Indonesia’s legal system requires more robust institutional reforms, increased judicial independence, and stronger mechanisms for accountability.